Боротьба з русифікацією у Глухівському повіті після революції 1905–1907 рр. Огляд дописів газети «Рада» - Мірошниченко, Н.О. (Сіверщина в історії України, 2025)
Стаття досліджує проблему боротьби з русифікацією у Глухівському повіті на початку XX століття на основі матеріалів газети «Рада». Використовуючи архівні джерела, автор аналізує соціокультурний контекст регіону, роль освіти, зокрема Глухівського учительського інституту, та вплив місцевої влади на процес русифікації. Стаття висвітлює ініціативи місцевих жителів, направлені на боротьбу з русифікацією регіону, а також системний опір місцевої адміністрації як-от земства та імперської влади загалом. Окремо простежено роль преси у формуванні національної свідомості. The article examines the issue of resistance to Russification in the Hlukhiv County at the beginning of the 20th century based on materials from the newspaper «Rada». Using archival sources, the author analyzes the socio-cultural context of the region, the role of education – in particular, the Hlukhiv Teachers’ Institute – and the influence of local authorities on the Russification process. The article highlights the initiatives of local residents aimed at countering Russification in the region, as well as the systemic resistance of the local administration, including the zemstvo and the imperial authorities in general. Special attention is paid to the role of the press in shaping national consciousness.